Komunikasi Krisis di Era New Media dan Social Media - Narayana Mahendra Prastya (Jurnal Komunikasi, 2011)
New media and social media have changed the practice of public relations. One area that changed is crisis communication. Because of these new technologies, crisis can be more complex. The pace of information, the uncertainty, and the rumors, are increasing. Public relations practitioners should include the new media and social media use in their crisis communication plan. Before doing that, public relations practitioners should change their mindset about social media and new media. The first part of this article contains introduction that describe the importance of communication in crisis management and the importance of social media and new media use in crisis communication. The second part is literature review, that consist of two themes: the concept about crisis communication; and crisis communication in the new media and social media era. The third part describes two cases from Indonesian corporation when they used social media and new media in crisis communication. Each cases explain the success story and the failed story in social media and new media use.